The impact of coupling a dynamic ocean in the Hurricane Analysis and Forecast System - Gramer, Lewis J.; Steffen, John; Aristizabal Vargas, Maria; Kim, Hyun-Sook (Frontiers in Earth Science, 2024)
Coupling a three-dimensional ocean-circulation model to an atmospheric model can significantly improve forecasting of tropical cyclones (TCs). This is true of forecasts for TC intensity (maximum sustained surface wind and minimum central pressure), but also structure (e.g., surface wind-field sizes). This study seeks to explore the physical mechanisms by which a dynamic ocean influences TC evolution, using an operational TC model. The authors evaluated impacts of ocean-coupling on TC intensity- and structure-forecasts from NOAA’s Hurricane Analysis and Forecast System v1.0B (HFSB), which became operational at the NOAA National Weather Service in 2023. The study compared existing HFSB coupled simulations with simulations from an identical model configuration in which the dynamic ocean coupling was replaced by a diurnally varying sea-surface temperature model. The authors analyzed TCs of interest from the 2020-2022 Atlantic hurricane seasons, selecting forecast cycles with small coupled track-forecast errors for analysis. The results show the link between dynamic, coupled ocean response to TCs, and coincident TC structural changes related to changing intensity and surface wind-field size. These results show the importance of coupling in forecasting slower-moving TCs and those with larger wind fields. However, there are unexpected instances where coupling impacts the near-TC atmospheric environment (e.g., mid-level moisture), ultimately affecting intensity forecasts. These results suggest that, even for more rapidly moving and smaller TCs, the influence of the ocean response to the wind field in the near-TC atmospheric environment is important for TC forecasting. The authors also examined cases where coupling degrades forecast performance. Statistical comparisons of coupled against uncoupled HFSB further show an interesting tendency: high biases in peak surface winds for the uncoupled forecasts contrast with corresponding low biases, contrary to expectations, in coupled forecasts; coupled forecasts also show a significant negative bias in the radii of 34 kt winds relative to National Hurricane Center best track estimates. By contrast, coupled forecasts show very small bias in minimum central pressure compared with a strong negative bias in uncoupled. Possible explanations for these discrepancies are discussed. The ultimate goal of this work will be to enable better evaluation and forecast improvement of TC models in future work.